Cultural Differences between Poland and Cambodia in the Context of Teaching Polish as a Foreign Language - Ludwicka, Aleksandra (Activation – innovation – acculturation. (Glotto)didactics and the migration crisis, 2024)
The subject of this article is to present cultural differences between Poland and Cambodia in the context of teaching Polish as a foreign language. The aim is to show how differences (or lack) in particular aspects affect the acquisition of the Khmer language and culture. The work uses the concept of culture dimensions proposed by Geert Hofstede.